Solution of the problem of the German population in Poland in the Polish underground political ideas = Rozwiązanie problemu ludności niemieckiej w Polsce w myśli politycznej Polski podziemnej - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The German invasion of Poland on September 1, 1939. opened up the possibility of establishing post-war Polish-German border on the Oder the Lusatian Neisse. After the war, all Germans were to be expelled from the Poland as a result of aggression of the Third Reich on Poland, occupation, crime, terror and expulsion of Poles. Only leq-wing parties considered this plan as dangerous for the post-war Poland. It considered German retaliation as dangerous. Western powers supported the expulsion of Germans from Poland, but not out of border on the Oder and the Lusatian Neisse. For this reason the Polish government in London limited its claim according to East Prussia, the Free City of Danzig and Silesia. The Goverment also wanted to keep a Riga border with the Soviet Union.
Keywords: polish underground; the problem of the German population; Second World War; polskie podziemie; problem ludności niemieckiej; II (druga) wojna światowa